Humboldt y el Colonialismo - Holl, Frank (HiN – Alejandro de Humboldt en la Red. Revista internacional de estudios humboldtianos, 2021)
AbstractDuring his American expedition Humboldt grappled intensively with the iniquities of colonialism. In the year 1803, for example, he noted „that the idea of a colony is itself an immoral idea, this idea of a land which is obliged to pay dues to another country.“ The colonial powers, wrote Humboldt, support intolerance, repression and slavery. However, he did not express his criticism in public during the expedition but entrusted it only to good friends and his diary. The lecture treats Humboldt's political stance during the expedition, based on human rights and his communicative role as a research traveller who, having returned to Europe, made his criticism public. Central to the lecture are examples of Humboldt's criticism of representatives of the colonial system. These make clear which important impulses the researcher gave to the independence movement and to the politicians of the young American states.